The Art of Evasion and 2024 Budget : Pragmatic Analysis (Seni Helah dan Perbahasan Belanjawan 2024 : Analisis Pragmatik) - Muhammad Qhidir, Mat Isa (Parliament of Malaysia, 2024)
The integrity of the administration of any governmentlargely depends on relevant and clear financial policies, for instance, Short-Term Plans or Annual Budgets. Periodically, the Annual Budget, the most important component of Parliamentary discourse, will be tabled for discussion, either to gain support or face criticism in both Houses of Representatives. Certainly, discussions and debates require politicians to master the art of rhetoric, analysis, and inference to navigate the dynamics of political legitimacy. For this purpose, the important document known as the Hansard serves as a substantial source, recording the strategies and art of Evasive Language in challenging-defending policies, addressing-mitigating issues, and strengthening-undermining the image that determines the integrity of the legitimacy of both the Governmentand and Opposition. However, previous corpus studies by Hansard on the topic of Evasive Response have focused only on the structural forms of debate. Therefore, employing three Pragmatic models, namely Harris’s Framework of Respons (1991), Thomas’s Notion of Implicator (1995), and Claymen’s Dimension of Resistance (2012), this qualitative study aims to analyse more complex, intense, and natural debate sessions, specifically the policy debate on the 2024 Budget. The findings reveal that all three types of Responses have some distinctive features, and their selection correlates with the scale of their impact on the image of the Government-Opposition. In addition, adhering to the Gricean Maxims (1975), the configuration of Evasive Language behavior is more easily defined and justified. Lastly, the discourse background at the policy level is more heterogeneous, thereby enriching the performative nature of Evasive Language.